2006
DOI: 10.14507/epaa.v14n13.2006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of language and high-stakes testing policies on elementary school English language learners in Arizona.

Abstract: This article reports the results of a survey of third-grade teachers of English Language Learners (ELLs) in Arizona regarding school language and accountability policies—Proposition 203, which restricts bilingual education and mandates sheltered English Immersion; the federal No Child Left Behind Act of 2001 (NCLB); and Arizona LEARNS, the state’s high-stakes testing and accountability program. The instrument, consisting of 126 survey questions plus open-ended interview question, was designed to obtain teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 8 publications
0
40
0
Order By: Relevance
“…Finally, for district administrators, changing practice may mean altering the ways they go about the task of making decisions or setting new policies, but it may also mean changing the way that they work in relation to each other and those in schools. 5 Like organizational change, it is important to remember that change in practice may not always be positive, as when teachers and administrators game the system (Booher- Jennings, 2005;Heilig & Darling-Hammond, 2008), take measures to narrow the curriculum (Diamond & Cooper, 2007;Hoffman, Assaf, & Paris, 2001;Marsh, Hamilton, & Gill, 2008;Ogawa, Sandholtz, & Scribner, 2004;Sloan, 2006;Wright & Choi, 2006), or make short-term, superficial changes in practice (Diamond & Cooper, 2007).…”
Section: Change In Practicementioning
confidence: 99%
“…Finally, for district administrators, changing practice may mean altering the ways they go about the task of making decisions or setting new policies, but it may also mean changing the way that they work in relation to each other and those in schools. 5 Like organizational change, it is important to remember that change in practice may not always be positive, as when teachers and administrators game the system (Booher- Jennings, 2005;Heilig & Darling-Hammond, 2008), take measures to narrow the curriculum (Diamond & Cooper, 2007;Hoffman, Assaf, & Paris, 2001;Marsh, Hamilton, & Gill, 2008;Ogawa, Sandholtz, & Scribner, 2004;Sloan, 2006;Wright & Choi, 2006), or make short-term, superficial changes in practice (Diamond & Cooper, 2007).…”
Section: Change In Practicementioning
confidence: 99%
“…The low levels of academic achievement (Fry & Lopez, 2012) and high rate of dropout (NCES, 2014) further necessitated the need to focus the study on Latino ELLs. Second, the study sought to 26 address the perceptions of ESL teachers because of the absence of ESL teachers' voices in the existing literature and the evidence that ESL teachers may spend the most instructional time with ELLs and have the deepest understanding of policy impact on ELLs (Wright & Choi, 2006). Third, the study was designed to examine the perceptions of teachers in a school district with a small percentage of ELLs because demographic data indicated that a growing number of ELL families are moving into school districts with traditionally small ELL populations (Capps et al, 2005).…”
Section: Purpose Of Studymentioning
confidence: 99%
“…Besides ideological critiques, studies have mostly noted programmatic changes at the district and/or state level (de Jong et al 2005;Gándara et al 2005;Garcia and Curry-Rodriguez 2000;Maxwell-Jolly 2000) or have analyzed the impact of the laws on student English language development and academic achievement by examining exit rates or standardized achievement test scores (e.g., Clark 1999;Grissom 2004;Hill 2004;Mahoney et al 2005;Pappano 2006;Parrish et al 2006;Sacchetti and Jan 2006;Wright 2005;Wright and Choi 2006). While the focus on these 'outer' policy layers can provide important insights, they leave out the central role that context and the beliefs of individuals within particular contexts play in policy processes (Ricento and Hornberger 1996;Stritikus and Wiese 2006).…”
Section: Teachers and Language Policymentioning
confidence: 99%
“…With some exceptions (e.g., Combs et al 2005;Sánchez 2006;Wright and Choi 2006), they have almost exclusively focused on Proposition 227 in California (Gándara et al , 2005Parrish et al 2006; and special issues of the Bilingual Research Journal [2000] and The Urban Review [2001]). These articles collectively highlight the chaotic nature of the initial implementation process in the absence of clear guidelines and the lack of sufficient professional development, collaboration, and resources (including access to native language resources) (Arellano-Houchin et al 2001;Gándara et al 2005;Gándara et al 2003).…”
Section: Teachers and Language Policymentioning
confidence: 99%